The Effect of Arumanis Mango Rind (Mangifera indica L) Extract as Antidiabetic in Rats Model - Ifmaily, Ifmaily; Firla, Afni; Fitriani, Putri Rizki (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
Arumanis  mango (Mangifera indica L) rind is one of the organic wastes containing flavonoid compounds. The objectives of this study were to find out the effect of arumanis mango rind extract on alloxan-induced blood glucose reduction in rats, to find out the most effective dose for reducing the levels of blood glucose in diabetic rats, and to find out the histopathology of the pancreas in diabetic rats.We used experimental method. In this study, 24 rats were divided into six groups consisting of I negative control, II positive control, III, IV, V different doses of 100 mg/kg BW, 200 mg/kg BW, 400 mg/kg BW and VI comparison group ( glibenclamide ). Groups II to VI were administered alloxan at 150 mg/kg BW for 3 days, and then the extract was administered to each group for 14 days, except group II. The levels of blood glucose were measured using a glucometer via the capillary of rat’s tail,  before and after induction and after administration of extract to all groups. The results are analyzed by the one-way ANOVA it showed significantly different results (p< 0.05 ). The extract of arumanis mango rind in all doses, had an effect on decreasing the level of blood glucose in diabetic rats effectively in dose of 400 mg/kg BW ( group V ) and histopathology desricptive results showed that arumanis mango rind extract could reduce damage to the pancreatic islet of Langerhans with histopathology of the exocrine glands and endocrine glands at group V was better than at group III and IV.